A multi-plug filtration (m-PFC) cleanup method based on carboxylic multi-walled carbon nanotubes for the detection of 14 perfluorinated compounds and dietary risk assessment of chicken, beef, and mutton collected from Shanghai markets. (December 2021) - Wang, Xianli; Zhang, Qicai; Zhao, Zhiyong; Song, Weiguo; Cheng, Lin; Yang, Junhua; Chen, Shanshan; Guan, Shuhui; Song, Wei; Rao, Qinxiong; Zhao, Zhihui
Abstract: Dietary intake is a major pathway of human exposure to perfluorinated compounds (PFCs). Livestock and poultry meats (chicken, beef, mutton) account for a significant proportion of dietary consumption in China, and thus it is crucial to investigate the levels and composition profiles of PFCs in consumer meats to assess and mitigate potential health risks. However, rapid and simple analytical methods for such investigations are lacking. This study addresses this shortcoming by developing a rapid filtration clean-up method using carboxylic multi-walled carbon nanotubes (CMWCNTs) for the detection of 14 PFCs. Good linearities (R 2  > 0.99) were obtained for all 14 PFCs in chicken, beef, and mutton. Recoveries ranged from 65 to 145% (except perfluorotetradecanoic acid, PFTeDA) with relative standard deviations (RSDs) lower than 16%. Method limits of detection (LODs) were between 0.12 and 0.83 ng g −1 d.w. Subsequently, this method was applied for the analysis of 46 livestock and poultry meat samples collected from markets in Shanghai. PFCs were detected in all samples with total concentrations of 1.61–4.27 ng g −1 wet weight (w.w) in chicken, 1.51–5.56 ng g −1 w.w in beef and 1.61–8.15 ng g −1 w.w in mutton. Perfluorooctanoic acid (PFOA) and perfluorobutanoic acid (PFBA) were the predominant compounds in these samples and accounted for over 92% of ΣPFCs. For regulated compounds such as PFOA, risk quotients (RQs) were determined to be much lower than 1. This suggests that chicken, beef, and mutton from Shanghai market pose very low PFC exposure risk to residents. However, high detection frequency of the unregulated PFBA demands further investigation of short-chain PFCs in consumer meats. Graphical abstract: Image 1 Highlights: Livestock and poultry meats is a major pathway of human exposure to PFCs. Lack of rapid and simple methods to detect PFCs in consumer meats. A m -PFC cleanup method based on CMWCNTs was developed to fast detect 14 PFCs in meats. PFBA was firstly examined in consumer meats and was the most abundant congener. Chicken, beef, and mutton from Shanghai markets were generally low PFC exposure risk.